Research on the heat transfer model of double U-pipe ground heat exchanger based on in-situ testing - Wang, Ruifeng; Shi, Mingchuan; Zhu, Ke; Yu, Jun; Ren, Wei; Yan, Guohong; Yin, Zhiqiang; Gao, Shujie (Frontiers in Energy Research, 2024)
The Double U-pipe ground heat exchanger, known for its simple process, cost-effectiveness, high heat exchange efficiency, and low thermal resistance, remains the predominant type of ground heat exchanger in today’s shallow geothermal energy development and utilization. In recent years, significant research has focused on the factors influencing heat transfer and the heat exchange performance of Double U-pipe ground heat exchangers through experimental testing methods. However, studies that integrate numerical simulation with in situ testing have been less common. Utilizing the cylindrical heat source model theory and the results of regional in situ thermal response tests, this paper develops a Double U-pipe ground heat transfer model by establishing physical, mathematical, and heat transfer geometric models. It evaluates the effects of varying inlet temperatures, flow rates, and initial ground temperatures on heat exchange efficiency under heating conditions. The results confirm the accuracy of the Double U-pipe ground heat exchanger model based on in situ testing. They indicate that increasing the temperature differential between the inlet and initial temperatures, raising the initial ground temperature, and moderately enhancing the flow rate can improve the system’s heat exchange efficiency.